EVALUASI KESESUAIAN LOKASI DAN JANGKAUAN PELAYANAN SEKOLAH MENENGAH UMUM DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Gloria Putri Pancarrani; Bitta Pigawati (Geoplanning: Journal of Geomatics and Planning, 2014)
Senior high school facilities is one of the settlement environment facilities that become supported facilities of settlement area. Determine of education facilities location is determined based location of student. The purpose of this condition is to make it easy student to range this education facilities location. Determine of education facilities location has been manage by government (The Regulation of ministre of Public Works No. 41/PRT/M/2007). The research aims to evaluate suitability of the location and service area of senior high school in Kebakkramat Sub-district. This research uses spatial analysis approach techniques to know region function and distribution of education facility location. The result shows that the senior high school location and range of service is suitable with mass transportation link and good access for student.